Cloning of putative ureG genes from Glomus intraradices and urease activities in tobacco arbuscular mycorrhizal roots (Scientia Agricola, 2009)
Even though the major benefit of arbuscular mycorrhizae is the increased uptake of phosphate from the soil solution and translocation to the plant, changes in the activity of enzymes involved in nitrogen (N) metabolism have been detected in mycorrhizal roots. Using differential display of reverse-transcripts of tobacco roots not-inoculated or inoculated with Glomus intraradices (Gi), we have cloned two partial cDNAs (NtGi2 and NtGi3). The presence of a conserved CobW/HypB/UreG domain and phylogenetic analyses suggest that NtGi2 and NtGi3 encode isoforms of urease accessory protein G (ureG) highly similar to ureG from fungi. The steady state levels of the putative ureG transcripts were shown to be higher in roots colonized by Gi, as compared to non-mycorrhizal controls. Urease activities were also determined in tobacco roots inoculated with Glomus clarum (Gc) or Gi and grown in substrate containing 50, 100 or 150 mg N kg-1 in the form of ammonium sulfate (N-AMS) or urea (N-URE). Urease activities were shown to be induced in mycorrhizal roots fertilized with 100 mg N-AMS kg-1. In Gc-colonized roots fertilized with N-URE, induction of urease activities was observed at the lowest N concentration. In contrast, at the highest N-URE concentration, suppression of urease activities was observed in Gc and Gi-colonized roots, as compared to non-mycorrhizal controls. Urease activities in roots were modulated by soil N availability and source, and arbuscular mycorrhizal fungal inoculation.